Fred McGraw Donner tentang al-Qur’an: Pemikiran dan Catatan Kritis terhadap Kesarjanaan Non-Muslim - Ahmad Labib Majdi; Iik Arifin Mansurnoor (JOURNAL OF QUR'AN AND HADITH STUDIES, 2021)
This paper aims to discuss Fred McGraw Donner’s thoughts on the Qur’an and the Qur’anic studies among non-Muslim scholars. By using a concept/thought studies research design and library research, this paper outlines Donner’s thoughts on the Qur'an, which is available on various works in the form of journal articles, book chapters, monographs, or review work. The findings of this paper claim that as historian Donner succeeded in presenting critical thoughts by not accepting traditional explanations at face value and not tending to reduce the Qur’an’s theological status and its historicity. On the issue of the historicity of the Qur’an, Donner has also offered three things or three steps that can be considered as a method in the search for the historical truth of the Qur’an. These three things are starting with the Qur’an text itself, comparing the hints inside it with sira literature, and looking at the religious phenomenon of the late antique Near East.